The Beatles and the Beatlesque: A Crossdisciplinary Analysis of Sound Production and Stylistic Impact - Martinelli, Dario; Bucciarelli, Paolo (Cham : Springer International Publishing : Imprint: Springer, 2023)
The Beatles and the Beatlesque address a paradox emanating from The Beatles' music through a cross-disciplinary hybrid of reflections, drawing from both, musical practice itself and academic research. Indeed, despite their extreme stylistic variety, The Beatles' songs seem to always bear a distinctive identity that emerges even more in similar works by other artists, whether they are merely inspired, derivative or explicitly paying homage. The authors, a musicologist and music producer, emphasize the importance of record production in The Beatles' music in a way that does justice not only to the final artifacts (the released songs) but also to the creative process itself (i.e., the songs "in the making"). Through an investigation into the work of George Martin and his team, as well as The Beatles themselves, this text sheds light on the role of the studio in shaping the group's eclectic but unique sound. The chapters address what makes a song "Beatlesque", to what extent production choices are responsible for developing a style, production being understood not as a mere set of technicalities, but also in a more conceptual way, as well as the aesthetics, semiotics and philosophy that animated studio activity. The outcome is a book that will appeal to both students and researchers, as well as, of course, musicophiles of all kinds.
Preface -- Introduction -- 1. A brief history of The Beatles in the studio -- 2. Style and sound -- 3. The difficulty of defining the Beatles style -- 4. Crossdisciplinary reflections: production vs. multimodality studies, narratology, and film studies -- 5. Birth and fortune of the "Beatlesque": Transmission of creativity and legacy -- Appendix -- Bibliography -- Index of names -- Index of songs, albums, and other artworks.
Keywords: Popular music; Motion pictures; Semiotics; Acoustical engineering; Aesthetics; Popular Music; Audio-Visual Culture; Semiotics; Engineering Acoustics; Aesthetics